Photo-Inactivation of Staphylococcus aureus by Diaryl-Porphyrins - Viviana Teresa Orlandi; Eleonora Martegani; Nicola Trivellin; Fabrizio Bolognese; Enrico Caruso (Antibiotics, 2023)
Photodynamic Antimicrobial Chemotherapy (PACT) has received great attention in recent years since it is an effective and promising modality for the treatment of human oral and skin infections with the advantage of bypassing pathogens’ resistance to antimicrobials. Moreover, PACT applications demonstrated a certain activity in the inhibition and eradication of biofilms, overcoming the well-known tolerance of sessile communities to antimicrobial agents. In this study, 13 diaryl-porphyrins (mono-, di-cationic, and non-ionic) P1–P13 were investigated for their potential as photosensitizer anti-Staphylococcus aureus. The efficacy of the diaryl-porphyrins was evaluated through photo-inactivation tests. Crystal-violet staining combined with viable count techniques were aimed at assaying their anti-biofilm activity. Among the tested compounds, the neutral photosensitizer P4 was better than the cationic ones, irrespective of their corresponding binding rates. In particular, P4 was active in inhibiting the biofilm formation and in impairing the viability of the adherent and planktonic populations of a 24 h old biofilm. The inhibitory activity was also efficient against a methicillin resistant S. aureus strain. In conclusion, the diaryl-porphyrin family represents a reservoir of promising compounds for photodynamic applications against the pathogen S. aureus and in preventing the formation of biofilms that cause many infections to become chronic.